(untitled) (Journal of the College of Basic Education, 2024)
One of the methods of green synthesis is the development of biological processes and methods for creating nanoparticles, which is an important development in the use of nanotechnology. This research aims to use the cardamom plant Elettaria Cardamomum to synthesize silver nanoparticles, which is a very safe, green, environmentally friendly and cheap method in most provinces of Iran and available in the market. ) and added to it at a temperature of (70⁰), and it was filtered with filter paper and centrifuged, and the reaction process was carried out with a solution of silver nitrate with different concentrations (1-2-3) moles and with a weight of (0.0162). - 0.0324 - 0.0486) dissolved in (100) ml of deionized water to prepare a silver nitrate solution and slowly added to the aqueous extract of the prepared plant (15-10-5 ml). Gradually at room temperature and over 48 hours on a magnetic rotor, it was determined that the synthesis process changed the color of the extract combined with the silver nitrate solution from yellow to dark brown, and then the extract was combined with the silver nitrate and the solution. It was washed with distilled water and each time it was placed in a centrifuge at 8000 rpm for 10 minutes each time to obtain silver nanoparticles. The active components of the cardamom plant were identified and it was found that it contains a group of flavonoids, a group of phenols, a group of alkaloids, resins, tannins, steroids, a saponin group, and also a group of fats..